If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -4 = 16 Reorder the terms: -4 + 4t = 16 Solving -4 + 4t = 16 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4t = 16 + 4 Combine like terms: -4 + 4 = 0 0 + 4t = 16 + 4 4t = 16 + 4 Combine like terms: 16 + 4 = 20 4t = 20 Divide each side by '4'. t = 5 Simplifying t = 5
| 8ef+5ef-ef= | | xy=6-x | | 6x+18=13x-45 | | 0.012x^2-0.583x+35.727=55 | | -3(4)+9=-57 | | 846=n-37 | | 11-2x=8-5x | | 2(2x+60)+2(5x)=360 | | w-9w=73-89 | | 11-18x-8x^2= | | 0.5d-0.75=0.6d | | log(0.8x+1)=log(0.8y+1)-log(1-u) | | 5x-18*4=36 | | 4z=28-0.25(4-16z) | | ln(0.8x+1)=ln(0.8y+1)-ln(1-u) | | 7-6x=4x-23 | | x^4-28x-288=0 | | 7-7x=37-14x | | 4y-2=12x | | 5y^2-14y+8=0 | | 1.5y+4=-15 | | 3x+9=51-9x | | -4c=-8 | | 7.9z-1.5=30.1 | | 5(2z-1)-4(z+4)=4(z+1) | | y=-0.296x^2+2.7x | | 6(m-3)+4=28 | | 6y=5y+y | | 10+20=16x-80 | | 10x+3x=26+x | | 6(3x-4)=12-2(2x-4) | | 5z^2+18z-8=0 |